Identity Politics and Prospective Leader Selection: A Perspective from Fiqh Siyasah - Ahmad Annizar; Zainul Fuad; M. Syukri Albani Nasution (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2024)
This research delves into the intricate dynamics of identity politics within the framework of selecting prospective leaders, with the overarching goal of reconciling perspectives from both the state and Islamic law to foster societal stability and harmony. Employing qualitative research methods, including observation, interviews, and documentation, the study embarks on a comprehensive exploration of political participation within Fiqh Siyasah. It underscores the imperative of entrusting leadership roles to individuals who demonstrate unwavering commitment to upholding Islamic principles in politics. This research shed light on the adaptable nature of Fiqh Siyasah, which continuously evolves to address society's evolving needs and challenges. Through a case study focusing on the political engagement of the Kotasan Village Community in the 2022 Village Head Election, the research elucidates the multifaceted dimensions of political participation within an Islamic context. Despite the inherent mandate to elect leaders for the betterment of societal welfare, the study reveals prevalent challenges, notably the pervasive influence of money-driven politics that often supersedes the foundational principles of Fiqh Siyasah. This research serves as a significant contribution to the discourse on identity politics and leadership selection, offering valuable insights into the nuanced interplay between religious principles and political realities in contemporary societies.